2006
DOI: 10.1007/s10592-006-9250-6
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the carinate pillsnail, Euchemotrema hubrichti: genetic structure on a small spatial scale

Abstract: Euchemotrema hubrichti (Pilsbry, 1940) is a polygyrid land snail known only from the Larue Pine Hills region of southwestern Illinois, USA. Despite the restricted range of the species, observations in the field suggested that patterns of genetic variation within E. hubrichti might show geographic structure. To assess the dispersal potential of E. hubrichti, a mark-recapture experiment was performed at two sites <100 meters apart. To evaluate the geographic distribution of genetic variation, a region of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The combinations of these factors amplify interpopulation divergence while minimizing intrapopulation variation. For example, using mark-recapture methods no dispersal was detected between two populations of the Carinate Pillsnail, Euchemotrema hubrichti separated by \100 m over a period of three years (Anderson, 2007). Such limited dispersal enables unique allele mutations to accumulate rapidly in each population thereby resulting in rapid genetic divergence between isolated populations.…”
Section: Inter-population Genetic Diversitymentioning
confidence: 99%
“…The combinations of these factors amplify interpopulation divergence while minimizing intrapopulation variation. For example, using mark-recapture methods no dispersal was detected between two populations of the Carinate Pillsnail, Euchemotrema hubrichti separated by \100 m over a period of three years (Anderson, 2007). Such limited dispersal enables unique allele mutations to accumulate rapidly in each population thereby resulting in rapid genetic divergence between isolated populations.…”
Section: Inter-population Genetic Diversitymentioning
confidence: 99%
“…Several studies have focused on the micro-scaled structure of land snail populations (Schilthuizen and Lombaerts 1994;Anderson 2007;Armbruster et al 2007a). Trochulus caelatus (formerly Trichia caelata) is a small terrestrial gastropod (shell height: 4 mm, width: 8 mm; Kerney et al 1983) endemic to the northwestern Swiss Jura Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses of nucleotide and haplotype diversity revealed that populations of E. acacioi present higher levels of genetic diversity when compared with populations of other invertebrate endangered species (Moya et al, 2004;Anderson, 2007;Strasser and Barber, 2009). Due to the lack of data about mutation rates (μ) for the COI gene in Onychophora, the population sizes could not be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influencing gene flow within and among animal populations is vagility. Species with low vagility are expected to have low levels of gene flow and high levels of population differentiation, and they are more sensitive to habitat loss or degradation (Bohonak, 1999;Anderson, 2007).…”
Section: Introductionmentioning
confidence: 99%